The interactive effect of anxiety sensitivity and negative smoking cessation cognitions on reductions in cigarette consumption during acute cessation. (June 2021) - Borges, A.M.; Versella, M.V.; Kibbey, M.M.; Hall, S.M.; Leyro, T.M.
Highlights: Anxiety sensitivity (AS) and cognitions predict 24-h cessation outcomes. High AS and intolerance of withdrawal interact to predict smaller reductions. High AS and lower success in quitting interact to predict smaller reductions. Abstract: Introduction: Anxiety sensitivity (AS) as well as negative cognitions about one's ability to quit smoking represent cognitive-affective vulnerabilities implicated in smoking cessation success. However, the extent to which one's perceived sensitivity to anxiety and cessation-related cognitions uniquely and interactively affect acute abstinence outcomes has not been examined. The current study examined the interactive effects of AS and cessation cognitions on percent reductions in cigarettes smoked during the first 24-h of a quit attempt. Methods: Adult cessation-motivated smokers (n = 64; M age = 34.21, SD = 11.49) completed a planned quit attempt. AS and cessation cognitions were evaluated prior to quit day. Percent cigarette reduction was assessed by number of cigarettes smoked the day before and during the first 24 h of the quit attempt. Results: Significant interactive effects between AS and cessation cognitions (i.e., expectation of success in quitting, intolerance of withdrawal symptoms, and lack of cognitive coping) were observed. Consistent with hypotheses, individuals reporting higher AS and a greater perceived ability to tolerate withdrawal as well as a greater expectation of success reported larger reductions in cigarettes post quit compared to those who did not endorse these beliefs. Unexpectedly, individuals reporting lower AS who did not endorse the belief that they should be able to tolerate withdrawal discomfort, or a lack of cognitive coping, reported larger reductions compared to those who did endorse this belief. Conclusion: AS may interact with specific cessation cognitions. Pre-cessation beliefs that individuals will be successful and be able to tolerate withdrawal symptoms may support cessation efforts.